“Red Dot Theory”: A Multifaceted Exploration of Urban Expression - MVIN, Bertrand (GSA - Graffiti and Street Art, 2023)
The project was divided into two distinct parts: 1. The street performance that consisted of painting the “red dot” hundreds of thousands of times all over the city to achieve a noticeable “visual invasion” and stimulate public reactions, 2. The artistic documentation that led to the creation of a serie of multimedia works, sometimes interactives, addressing various sociological, urban, and anthropological topics, as well as several artistic notions such as symbolism or situationism. This artist talk will begin by providing an introduction to the performance’s process and protocol. This will be followed by a curated selection of the artist’s project documentation and related multimedia works, which will offer an in-depth exploration and a focus on its interactivity with the public. Finally, as a brief conclusion, we will witness the seamless alignment of “The Red Dot Theory” with the conference theme of “Numbers,” opening the door to a wider discussion. Through its deconstruction of tagging, the project showcases the influential role of numerical elements in urban creativity, exemplified by the symbolic visual invasion of countless “red dots” throughout Barcelona.